Investigation of Lithium Polyacrylate Binders for Aqueous Processing of Ni‐Rich Lithium Layered Oxide Cathodes for Lithium‐Ion Batteries. Issue 11 (3rd May 2022) - Reissig, Friederike; Puls, Sebastian; Placke, Tobias; Winter, Martin; Schmuch, Richard; Gomez‐Martin, Aurora
Abstract: Ni‐rich layered oxide cathodes are promising candidates to satisfy the increasing energy demand of lithium‐ion batteries for automotive applications. Aqueous processing of such materials, although desirable to reduce costs and improve sustainability, remains challenging due to the Li + /H + exchange upon contact with water, resulting in a pH increase and corrosion of the aluminum current collector. Herein, an example was given for tuning the properties of aqueous LiNi0.83 Co0.12 Mn0.05 O2 electrode pastes using a lithium polyacrylate‐based binder to find the "sweet spot" for processing parameters and electrochemical performance. Polyacrylic acid was partially neutralized to balance high initial capacity, good cycling stability, and the prevention of aluminum corrosion. Optimized LiOH/polyacrylic acid ratios in water were identified, showing comparable cycling performance to electrodes processed with polyvinylidene difluoride requiring toxic N ‐methyl‐2‐pyrrolidone as solvent. This work gives an exemplary study for tuning aqueous electrode pastes properties aiming towards a more environmentally friendly processing of Ni‐rich cathodes. Abstract : Sweet spot : Ni‐rich layered oxide cathodes are promising candidates to satisfy the demand for batteries for automotive applications. Aqueous processing of such materials is challenging due to the Li + /H + ‐exchange in water. Herein, an example is given for tuning the properties of aqueous electrode pastes by varying LiOH/polyacrylic acid ratios as binder and finding the "sweet spot" between processing and electrochemical performance.